PENGARUH TRANSAKSI DIGITAL BANKING TERHADAP FEE BASED INCOME DI SEKTOR PERBANKAN - Syahrani, Sefiza; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This study aims to analyze the influence of digital banking transactions on fee-based income in the banking sector. In the era of digital transformation, banks face the challenge of adapting to technological innovations that can increase cost-based revenue. The method used in this study is a qualitative approach with data collection techniques through in-depth interviews and observations at several banks that implement digital banking services. The results show that digital banking transactions significantly contribute to the increase in fee-based income, with factors such as the number of transactions and customer satisfaction being the main keys. The prospects of this study show that further development in digital banking services can increase the competitiveness of banks and provide added value for customers.